A meta-analysis of randomized control trials of surgical methods with osteosarcoma outcomes. Issue 1 (December 2017) - He, Xiaojun; Gao, Zhenzhen; Xu, Hongwei; Zhang, Zhongwei; Fu, Peng
Abstract Background Osteosarcoma is a high malignant neoplasm, and conflicting findings have been reported on the survival and function recovery of osteosarcoma patients experiencing limb salvage or amputation. In the present study, we compared limb salvage surgery (LSS) with amputation in clinical outcomes of osteosarcoma patients by a meta-analysis. Methods The survival rate of osteosarcoma patients was collected from research reports from CNKI, MEDLINE, EMBASE, the Cochrane Database, and Google Scholar till April 30, 2016. The quality of including articles was evaluated by two independent reviewers. Differences between patients undergoing limb salvage surgery and amputation were analyzed based on postoperative survival rates. Results Ten articles were included according to selection criteria. There were 1343 patients in total from these studies. Our results showed that there was no significant difference between limb salvage surgery and amputation according to local recurrence; however, patients with limb salvage surgery had a higher 5-year overall survival. Conclusions LSS results in higher 5-year survival rates and better survival, while not increasing the risk of local recurrence. This study provided more evidences to support limb salvage surgery as a considerable treatment of osteosarcoma patients.